Kuliah Kerja Nyata (KKN) Gerakan Mahasiswa Peduli Stunting dengan Sosialisasi dan Pemberian Makanan Tambahan (PMT) Di Desa Paseh Kidul, Kecamatan Paseh, Kabupaten Sumedang: Pengabdian - Nizar Husni Halim; Tasya Augustiya; Dyah Safitri; Naiyla Septiani; Ghina Shafa Kamila; Izudin Al Mukhtar; Lintang Khaerunisa; Mila Kamelia Matmi; Nazwa Salsabila Nuryadin; Novia Fitriani; Rizki Abd.Rahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Stunting remains a serious health problem in Indonesia, particularly in rural areas such as Paseh Kidul Village, Paseh District. Lack of education about nutrition and proper parenting practices are key factors contributing to this situation. A Community Service (PKM) activity by students from the Muhammadiyah University of Bandung (UMB) Community Service Program (KKN) aims to increase public understanding of stunting prevention through an educational and participatory approach. The methods used in this activity included nutrition counseling through a seminar titled "Rempug Stunting," featuring speakers from the local Community Health Center (Puskesmas), and the provision of supplementary feeding (PMT). Observations showed high community enthusiasm for this activity and increased participant knowledge about the importance of balanced nutrition in preventing stunting from an early age. This community service demonstrates that a community-based approach is effective in raising awareness and can be replicated in other regions as a concrete step towards reducing stunting rates in Indonesia.